2010
DOI: 10.1021/ac9029373
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Protein Processing Steps on a Droplet Microfluidics Platform for MALDI-MS Analysis

Abstract: A droplet-based (digital) microfluidics platform has been developed to prepare and purify protein samples for measurement by matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS). Liquid droplets are moved in air by sequentially applying an electric potential to an array of electrodes patterned beneath a hydrophobic dielectric layer. We show that a complete integrated sequence of protein processing steps can be performed on this platform, including disulfide reduction, alkylation, and enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 69 publications
0
72
0
Order By: Relevance
“…77 Here, we report an integrated method for implementing three discrete processing steps, including proteomic sample reduction, alkylation, and digestion; this paper joins related work 52,126,127 in demonstrating the compatibility of DMF with multistep proteomic sample processing. The qualitative and quantitative data presented here suggest that DMF is capable of highly repeatable sample processing, and thus may be a useful new tool for standardized proteomics analyses.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…77 Here, we report an integrated method for implementing three discrete processing steps, including proteomic sample reduction, alkylation, and digestion; this paper joins related work 52,126,127 in demonstrating the compatibility of DMF with multistep proteomic sample processing. The qualitative and quantitative data presented here suggest that DMF is capable of highly repeatable sample processing, and thus may be a useful new tool for standardized proteomics analyses.…”
Section: Introductionmentioning
confidence: 80%
“…[49][50][51][52] In DMF, discrete microdroplets are manipulated electrostatically on an array of electrodes coated with a hydrophobic, dielectric insulator. 53,54 The classical characterization of droplet movement in DMF is based on a thermodynamic approach using the Young-Lippman equation (Eq 1), 55,56 where change in contact angle, , is a function of applied voltage, V. Here,   is the contact angle when the electric field across interfacial layer is zero, ε r is the relative permittivity of the dielectric, ε o is the permittivity of free space,  is the is the liquid-filler media surface tension, and d is the dielectric thickness.…”
Section: Digital Microfluidicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the digestion of lysozyme, the digestion of BSA by TY-microreactor at 50 °C efficiently occurred but not at 30 °C. The sequence coverage of 37% (201/583 amino acids) was higher compared with that of in-solution digestion (26%, 151/583 amino acids) and was better or comparable to those of a thermal (Liu et al, 2009;Sim et al, 2006) or chemical denatured BSA (Li et al, 2007a;Chatterjee et al, 2010) or the reduced BSA (Ma et al, 2008) by the reported trypsin-microreactors (24-46%). In addition, the number of identified disulfide bonds was 10 of 17, which is superior to 6 obtained by in-solution digestion.…”
Section: In Addition It I S P O S S I B L E T H a T O U R M S S Y S mentioning
confidence: 85%
“…Chatterjee D et al showed that a complete integrated sequence of protein processing steps could be performed on droplet-based microfluidics platform, including disulfide reduction, alkylation, and enzymatic digestion, followed by cocrystallization with a MALDI matrix and analysis of the sample in situ by MALDI-MS [18]. In 2009, Jebrail M J et al reported the development of an automated microfluidic method for extracting proteins from heterogeneous fluids by precipitation [19].…”
Section: Peptide and Protein Analysismentioning
confidence: 99%